2020
DOI: 10.1002/jip.1562
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural themes in Spanish missing persons cases: An empirical typology

Abstract: The high number of missing person reports that occur globally each year highlights the need for research in this academically neglected field. This research focuses on establishing whether there are different scenarios or behavioural themes that consistently appear in missing person cases in Spain, which could assist the police investigation process. A representative sample of 341 missing person police reports was collated and up to 27 behaviours, which occur during the disappearance, have been codified, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 30 publications
3
10
2
Order By: Relevance
“…Our analysis indicated that criminal disappearances occur under various circumstances. This finding is novel and contrasts with previous studies that have classified missing person cases in a criminal context in a single group (Biehal et al., 2003; Foy, 2016; García‐Barceló et al., 2020; Henderson et al., 2000; Payne, 1995). This finding is novel and contrasts with previous studies tha have classified missing person cases in a criminal context in a single group (Biehal et al., 2003; Foy, 2016; García‐Barceló et al., 2020; Henderson et al., 2000; Payne, 1995).…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…Our analysis indicated that criminal disappearances occur under various circumstances. This finding is novel and contrasts with previous studies that have classified missing person cases in a criminal context in a single group (Biehal et al., 2003; Foy, 2016; García‐Barceló et al., 2020; Henderson et al., 2000; Payne, 1995). This finding is novel and contrasts with previous studies tha have classified missing person cases in a criminal context in a single group (Biehal et al., 2003; Foy, 2016; García‐Barceló et al., 2020; Henderson et al., 2000; Payne, 1995).…”
Section: Discussioncontrasting
confidence: 94%
“…The multidimensional scale analysis allowed García‐Barceló et al. (2020) to identify similar intentional dimensions as was found in Bonny's et al.’s (2016) classification (i.e., intentional dysfunctional, intentional escape, unintentional accidential/drif ), and one new category labelled ‘ unintentional criminal ’ reflecting an individual unintentionally missing related to criminal facts.…”
Section: Who Are the Missing Persons?mentioning
confidence: 70%
See 3 more Smart Citations